PENGEMBANGAN PETUNJUK PRAKTIKUM BIOLOGI DAN INSTRUMEN PENILAIAN KINERJA PRAKTIKUM BERBASIS MODEL PEMBELAJARAN KOOPERATIF DAN EFEKTIVITASNYA TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMA/MA KELAS XI - St. Rahmadani; Jamaluddin -; Lalu Zulkifli (Postgraduate, University of Mataram, 2015)
The aims of this study were: 1) to develop a biology practical guidance based on TGT cooperative models equipped with practical performance assessment instrument; 2) to determine the characteristics and suitability of products than have been developed; 3) to know it’s effectiveness in critical thinking abilities on biology subject of students in class XI. Product development process in this study by following Borg and Gall’s Development. The result of the expert validation by 3 validators showed that each of the average score in biology practical guidance based on TGT and practical performance assessment instrument were 4,41 and 4,48 and categorized as “very good”. Limited testing conducted on 10 students with high, medium, and low ability. The result of limited testing showed that each of percentage score average in biology practical guidance based on TGT and practical performance assessment instrument were 82,67% and 83,33% and categorized as “very good”. Field trial testing using a pre-test post-test control group design. The data of critical thinking abilities are tested in this study consist of 5 indicator skills: (1) formulate the problem; (2) recognize the existence of a logical relationship between issues; (3) collect and collate information; (4) asses and evaluate the statement of facts; (5) Make some conclude were needed. Data analysis were performed using two independent sample test formula by SPSS 20 for windows. The analysis showed that the critical thinking abilities for indicator 1, 2, 3, and 5 of experimental group different from the control group, while the fourth indicator not different. Data analysis equipped with calculation of the value of n-gain to determine the effectiveness of learning by using product that have been developed. The result of the data analysis showed that the value of n-gain in experimental groupis equal to 0,71 and categorized as “high”.